Lavapiés dixit: notes for visiting the revitalization of historical downtowns and their housing - Delgado, Miguel Ángel (2018)
It is a common idea thinks that the cultural heritage includes an essential and dynamic menu of human activity. If the historical centers means privileged communities in quantity and quality dimensions, if it is possible understand that the right management of this cultural heritage can become an increase of quality of life of these communities. The analysis of cultural heritage management’s cases experienced in European historical centers as Madrid (Spain) which developed experiences about it helps to develop a panoramical view and to organize this data in a systematic way of “learned lessons”.